Impact of elevation, latitude and longitude on fish diversity in Godavari River - Sandeep R. Rathod; Gulab D. Khedkar (Journal of Research in Biology, 2011)
India is very rich in biodiversity, India supports about 10% of the world’s biological diversity, with just 2% of world land area. Therefore India is the seventh richest biodiversity in the world. The India has Himalaya Mountain, Eastern Ghat, Western Ghats Indo-gangetic plain, Deccan plateau, desert, coasts are all present in it. In India many type of river also present, one of the river Godavari River is the second largest river in India. Fish biodiversity studies were undertaken during January-2008 to Decemeber-2008 to census and commercially important fishes in the Godavari River. The present paper deals with the variety and abundance of fresh water fishes in Godavari River with reference to the elevation, latitude and longitude. Two sampling points were selected with different elevation latitude and longitude. The Results of the present investigation reveal the occurrence of 53 fish species belonging to 9 orders, 21 families and 37 genera. Among the collected species two sampling site species composition were so different. Species composition in Gangapur dam is lower than the Rajahmundry dam. In species composition order Cypriniformes was most dominant to both sampling site.